The X-Ray Binary KS 1731{260: Possible Analogy with Her X-1 - Vojtěch Šimon (Acta Polytechnica CTU Proceedings, 2014)
The X-ray binary with the neutron star (NS), KS 1731-260, displays superorbital cycle similar to that in Her X-1. The accretion disk had the memory of the cycle-length even when this modulation sometimes disappeared in the main outburst of KS 1731-260, and during anomalous low state in Her X-1. The disk still existed during such seasons. Although irradiation of the disk by X-rays is a viable explanation for the disk precession and warping (see model of Foulkes et al.), the mechanisms which give rise to the observed X-ray modulation are quite dierent for each of these systems. Variable absorption can explain this cycle only in Her X-1. We propose a variable mass accretion rate onto the NS in KS 1731-260 due to a highly variable impact of the inflowing mass stream with the changing phase of the cycle.